Natality Detail File, 1981: (United States) ([Verlag nicht ermittelbar], 2004)
This collection provides information on live births in the United States during calendar year 1981. The natality data in this file are a component of the vital statistics collection effort maintained by the federal government. Geographic variables of residence for births include the state, county, city, population, division and state subcode, Standard Metropolitan Statistical Area (SMSA), and metropolitan/non-metropolitan county. Other variables include the race and sex of the child, the age of the mother, mother's education, place of delivery, person in attendance, and live-birth order. The natality tabulations in the documentation include live births by age of mother, live-birth order, and race of child, live births by marital status of mother, age of mother, and race of child, and live births by attendant and place of delivery.